The Politics of Breathing Troubles in COVID-19: Pandemic Inequalities and the Right to Breathe across India and Germany - Nasima Selim (Medicine Anthropology Theory, 2022)
‘Breathing trouble’ refers both to a biopolitical process and a metaphor for the current global condition. This Position Piece draws inspiration from the ‘universal right to breathe’ frame suggested by Joseph-Achille Mbembe (2021a) to discuss pandemic inequalities in Kolkata (India) from a location in the global north, Berlin (Germany), where the author currently lives and works. Drawing from the circumstances surrounding the interruption of my fieldwork in urban India, I argue how the border-crossing pandemic and the choking politics of the ruling governments in India and Germany are entangled in the production of pandemic inequalities. The coeval discussions of lived experiences and political grievances ‘there’ (India/Kolkata) and the critical questioning of the image of India from ‘here’ (Germany/Berlin) invite an understanding of breathing beyond its purely biological function to what we have in common, as the universal right to breathe. Such framing may help anthropologists to reattune to spatial, temporal, and ethical dimensions of excess empirical events in the constantly changing yet simultaneous pandemic realities.